Health Effect: Gadget Use and Addiction During Pandemic Covid-19 Session - Ramlan, Rohaizan; Mohd Tajuddin, Nurul Izzati (Research in Management of Technology and Business, 2022)
Technology, such as a smartphone or other gadget, is the art or skill of solving a problem, improving an existing solution to a problem, reaching a goal, and performing a specific function. However, if used excessively, people will develop a gadget addiction and suffer negative health consequences. Therefore, this study is to identify mobile applications or social media most used and health affected while addicted to the gadget. The researcher conducted the quantitative analysis by collecting online questionnaires and analysing the data using the Best Worst Method (BWM). The number of respondents for the questionnaire is 104, which is 27 percent from the sampling of 384 respondents. Of 104 respondents, only 70 were accepted, while 34 respondents rejected due to invalid answers. The questionnaire was distributed online at random via social media platforms such as Facebook, WhatsApp, Twitter, Instagram, email, and face-to-face. Based on the finding, communication is the most used mobile application, followed by productivity, multimedia, games, online learning and e-learning. Meanwhile eye strain is most affects health followed by sleep routine/ insomnia, physical health, mental health and germs. In contrast, the least used mobile application is E-learning and germs for the least affected the health.